2002
DOI: 10.1152/jn.2002.88.1.475
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Interleukin-6 Exposure Alters Electrophysiological Properties and Calcium Signaling in Developing Cerebellar Purkinje Neurons in Culture

Abstract: The cytokine interleukin-6 (IL-6) is chronically expressed at elevated levels within the CNS in many neurological disorders and may contribute to the histopathological, pathophysiological, and cognitive deficits associated with such disorders. However, the effects of chronic IL-6 exposure on neuronal function in the CNS are largely unknown. Therefore using intracellular recording and calcium imaging techniques, we investigated the effects of chronic IL-6 exposure on the physiological properties of cerebellar P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 51 publications
3
37
1
Order By: Relevance
“…It has been reported that IL-6 acts on the target cells and promotes dimerisation of gp130, a signaltransducing subunit coupled with the IL-6 receptor (23,28), which is confirmed in our experiments (Fig. 1b and c).…”
Section: Interleukin-6 Inhibits Voltage-gated Sodium Channel Activitysupporting
confidence: 91%
“…It has been reported that IL-6 acts on the target cells and promotes dimerisation of gp130, a signaltransducing subunit coupled with the IL-6 receptor (23,28), which is confirmed in our experiments (Fig. 1b and c).…”
Section: Interleukin-6 Inhibits Voltage-gated Sodium Channel Activitysupporting
confidence: 91%
“…Chronic exposure to IL-6 at a low concentration (1 ng/ml) enhanced Purkinje neurons spike firing, whereas chronic exposure to a higher concentration of IL-6 (10 ng/m) resulted in an inhibition of spike firing (Nelson et al, 2002). Chronic exposure to IL-6 also elevated resting Ca 2+ levels, increased the magnitude of intracellular Ca 2+ signals evoked by activation of group I metabotropic glutamate receptors, enhance Ca 2+ signaling induced by excitatory transmitters and membrane depolarization in the cultured Purkinje neurons (Nelson et al, 2004, 2002). All of these effects of IL-6 could significantly alter synaptic transmission involving the Purkinje neurons.…”
Section: Studies In Vivo and Vitro Have Established That Il-6 Has mentioning
confidence: 99%
“…According to the monocyte-T-lymphocyte hypothesis the immune system plays a key role in determining someone's personality and temperament, through synthesis, release and uptake of monoamines in the central nervous system [25,33,34]. Decreased or increased expression of synaptic plasticity, neurogenesis, and neuromodulation through basal ganglia, the frontal cortex and activity of the hypothalamus-pituitary axis (HPA) affect the limbic system and influence its various activations [26,27,35,36,37,38]. Thus, the complex of PEN traits and personality (temperament) is conditioned by many factors [39].…”
Section: Introductionmentioning
confidence: 99%